The Critique of the Book of the Modest State, the Modern State, Strategies for Another Change About the Modest Leviathan - Hamid Reza Malek Mohammadi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The contrast between the two phenomena of the demands of the new era and state behavior is among the issues that propel writers from various fields from management to sociology and political science. Critical papers, neutral papers, and papers advocate of the behavior of the state and the bureaucratic system are three aspects that stand out in this regard. Meanwhile, Michel Crozier, a writer sociologist and critic of state behaviors and bureaucracy, examining the post-World War II French states, finds them to have self-knowledgeable ideas and self-powerful imagination, but he believes that the developments of the era along with the failures of these states in achieving social and economic goals, especially in areas such as education and health, reveals the necessity of a fundamental rethinking of the state nature; a nature that  must be reflected in modesty of state. He views modern state as impossible without modest politics.